The Star of David on the parapet of the veranda - Mumbai Archive Project (Jio Institute, 2024)
The Star of David (a six-pointed star recognised as a symbol of Judaism) features in pairs of two on the parapet of the veranda. A flower motif is placed in the central part of the hexagram. The sets are separated by balusters. The presence of this Jewish symbol may be associated with the previous owners of the building, who could have been Baghdadi Jews, who had a sizable population living in Mazagaon in the 19th century but have since migrated to other countries.